The comparison of site spider “biodiversity quality” in Portuguese protected areas - Feest, Alan; Cardoso, Pedro (Ecological Indicators, 2012)
Spiders at 23 Portuguese protected area sites were sampled (pitfall trapped) over 10-month periods. The data allowed for a “biodiversity quality” assessment consisting of the following indices: Species Richness, Biomass, Simpson Index, Species Conservation Value Index and Population Density. These “biodiversity quality” characteristics were reviewed for relative indication of site spider “biodiversity quality”. Spiders are proposed as a group of organisms that could be used to indicate part of the “biodiversity quality” of a site since they can be sampled in a standardised way and yield biodiversity indices for comparison spatially and temporally. The approach adopted in this paper allows a range of “biodiversity quality” indices to be measured for spiders in Portuguese protected areas which, in turn requires decisions from scientists, managers and politicians on what element or characteristic of biodiversity it is intended to be targeted.
Keywords: biomass; Simpson Index; Site ranking; Species Conservation Value Index (SCVI); Species richness

Assessing spider species richness and composition in Mediterranean cork oak forests - Cardoso, Pedro; Gaspar, Clara; Pereira, Luis C; Silva, Israel; Henriques, Sérgio S; da Silva, Ricardo R; Sousa, Pedro (Acta Oecologica, 2008)
Semi-quantitative sampling protocols have been proposed as the most cost-effective and comprehensive way of sampling spiders in many regions of the world. In the present study, a balanced sampling design with the same number of samples per day, time of day, collector and method, was used to assess the species richness and composition of a Quercus suber woodland in Central Portugal. A total of 475 samples, each corresponding to one hour of effective ﬁeldwork, were taken. One hundred sixty eight species were captured, of which 150 were recorded inside a delimited one-hectare plot; this number corresponds to around 90% of the estimated species richness. We tested the effect of applying different sampling approaches (sampling day, time of day, collector experience and method) on species richness, abundance, and composition. Most sampling approaches were found to inﬂuence the species measures, of which method, time of day and the respective interaction had the strongest inﬂuence. The data indicated that fauna depletion of the sampled area possibly occurred and that the inventory was reaching a plateau by the end of the sampling process. We advocate the use of the Chao estimators as best for intensive protocols limited in space and time and the use of the asymptotic properties of the Michaelis–Menten curve as a stopping or reliability rule, as it allows the investigator to know when a close-to-complete inventory has been obtained and when reliable non-parametric estimators have been achieved.
Keywords: araneae; Arrábida; Biodiversity assessment; iberian peninsula; methodology; Portugal; Quercus suber; Richness estimators; Semi-quantitative sampling; Stop-rules

Assessing spider species richness and composition in Mediterranean cork oak forests - Cardoso, Pedro; Gaspar, Clara; Pereira, Luis C.; Silva, Israel; Henriques, Sérgio S.; da Silva, Ricardo R.; Sousa, Pedro (Acta Oecologica, 2008)
Semi-quantitative sampling protocols have been proposed as the most cost-effective and comprehensive way of sampling spiders in many regions of the world. In the present study, a balanced sampling design with the same number of samples per day, time of day, collector and method, was used to assess the species richness and composition of a Quercus suber woodland in Central Portugal. A total of 475 samples, each corresponding to one hour of effective ﬁeldwork, were taken. One hundred sixty eight species were captured, of which 150 were recorded inside a delimited one-hectare plot; this number corresponds to around 90% of the estimated species richness. We tested the effect of applying different sampling approaches (sampling day, time of day, collector experience and method) on species richness, abundance, and composition. Most sampling approaches were found to inﬂuence the species measures, of which method, time of day and the respective interaction had the strongest inﬂuence. The data indicated that fauna depletion of the sampled area possibly occurred and that the inventory was reaching a plateau by the end of the sampling process. We advocate the use of the Chao estimators as best for intensive protocols limited in space and time and the use of the asymptotic properties of the Michaelis–Menten curve as a stopping or reliability rule, as it allows the investigator to know when a close-to-complete inventory has been obtained and when reliable non-parametric estimators have been achieved.
Keywords: araneae; Arrábida; Biodiversity assessment; iberian peninsula; methodology; Portugal; Quercus suber; Richness estimators; Semi-quantitative sampling; Stop-rules

Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G; Serrano, Artur R M (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness

Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G; Serrano, Artur R M (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness

Indicator taxa of spider (Araneae) diversity and their efficiency in conservation - Cardoso, Pedro; Silva, Israel; de Oliveira, Nuno G.; Serrano, Artur R. M. (Biological Conservation, 2004)
A considerable number of alternative approaches have been suggested during the last years to predict species richness of a given taxon, while retaining information on the identities of the observed individuals. Such information can be extremely useful for choosing conservation priority areas, either by using raw richness values or, preferentially, by considering the complementarity between potential sites. Among the most popular approaches is the use of indicator taxa. Both one single family and a group of several families are here tested in their ability to predict the number of spider (Araneae) species independently of sampling eﬀort, geographical location and type of habitat. We use data from three Portuguese protected areas as a test case. A two-family indicator group – Gnaphosidae and Theridiidae – is found to be a good surrogate of species richness, even if caution is needed regarding the comparison of sites with considerably diﬀerent sampling eﬀort or vegetation cover. No single family can be seen as a good surrogate of the totality of spiders. In addition, only a group of the two mentioned families is found to be eﬃcient and reliable either when used to rank sites according to taxa richness or for determining near-minimum sets of sites for conservation. We therefore recommend surrogacy with this indicator group as a promising approach for the prediction of spider species richness or evaluation and ranking of areas according to their conservation importance. The reached conclusions should uphold for Portugal and the entire Mediterranean region.
Keywords: Complementarity; estimation; Mediterranean; Portugal; Species richness